2013
DOI: 10.1186/1471-2458-13-858
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative case study of child protection issues in the Indian construction industry: investigating the security, health, and interrelated rights of migrant families

Abstract: BackgroundMany of India’s estimated 40 million migrant workers in the construction industry migrate with their children. Though India is undergoing rapid economic growth, numerous child protection issues remain. Migrant workers and their children face serious threats to their health, safety, and well-being. We examined risk and protective factors influencing the basic rights and protections of children and families living and working at a construction site outside Delhi.MethodsUsing case study methods and a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Families also reported lack of familiarity with health systems in urban areas especially when they had to locate services at a new location each time. These findings reflect similar experiences elsewhere, where households delay seeking healthcare for sick children because of distance or high out of pocket expenditure contributing further to morbidity and mortality [4, 62, 63].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Families also reported lack of familiarity with health systems in urban areas especially when they had to locate services at a new location each time. These findings reflect similar experiences elsewhere, where households delay seeking healthcare for sick children because of distance or high out of pocket expenditure contributing further to morbidity and mortality [4, 62, 63].…”
Section: Discussionsupporting
confidence: 84%
“…In the city, migrant households mostly engage in temporary work that are characterized by low wages, insecure jobs, harsh recruitment regimes and economic vulnerability, which are known to be typical of informal work environments [2, 3]. A crucial aspect of labour migration in India is that many migrant households move with their entire families including children2 [4, 5]. Previous research in India has shown that even though migration provides economic opportunities to households, migrant children face several disadvantages in the destination region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty creates multiple stressors for families, including unemployment, substandard housing and schooling, exposure to violence, substance abuse, inadequate health care and parental absence (Staveteig & Wigton, 2005; Betancourt et al, 2013) leading to impoverishment in different aspects of child caregiving (De Wolff & van IJzendoorn, 1997; Walker et al, 2007). Attachment security in late childhood and adolescence is recognized as an important protective factor for different type of psychopathology later in life (Moretti & Peled, 2004).…”
Section: Children Attachment and Economic Insecurity: An Overviewmentioning
confidence: 99%
“…For children, school teachers are required to implement "one to one, one to one" approach to child care, to care for and help children grow; for the elderly, the elderly can arrange regular visits to families, regularly arrange doctors' physical examination [10]. Especially in the rural township government should increase investment in rural public health, accelerate the construction and transformation of township hospitals and village clinics; the construction of urban and rural social security system, improve the medical security level of farmer participation, to further promote the new rural endowment insurance policy; improve the rural elderly, left behind children, elderly people living alone and other special survival in the crowd, to create a good social atmosphere for the whole society to care for the people left behind.…”
Section: Strengthening the Management Of The Rural Society And Solvinmentioning
confidence: 99%